Unloving Mothers: Jesuit Knowledge Production on Abortion and Infanticide in Japan in the Sixteenth and Seventeenth Centuries*. - ZAMPOL D'ORTIA, LINDA (Journal of Religious History, 2025)
The article examines the narratives created by Jesuit missionaries regarding abortions and infanticides in Japan during the sixteenth and seventeenth centuries. It highlights how these missionaries, while acknowledging the prevalence of such practices, framed them through a European lens that often depicted Japanese women as lacking maternal love and moral understanding. The Jesuits attributed these acts to socio-economic factors and religious beliefs, while also attempting to promote their own Christian values as a solution. The analysis reveals a shift in the missionaries' narratives over time, from viewing Japanese women as inherently cruel to recognizing their ignorance and the need for proper emotional guidance in motherhood. Ultimately, the article illustrates the complexities of cultural interpretation and knowledge production by European missionaries in Japan.